Genetic Diversity of Bovine Viral Diarrhea Virus Infection in Goats in Southwestern China. (18th November 2018) - Deng, Yu; Wang, Silu; Liu, Runxia; Hao, Guiying
Abstract : Bovine viral diarrhea virus (BVDV) affects cows, pigs, sheep, goats, and other ruminants, as well as some wild animals. BVDV causes considerable economic losses every year and many countries have developed programs aimed at the eradication of this disease. The genetic diversity of BVDV in diseased goats has never been described in southwestern China. Thus, in this study, we applied antigen-capture ELISA and RT-PCR to survey the infection rate of BVDV in diseased goats in this region. Our results demonstrated that the average BVDV infection rate in goats was 17.51%, with all positive samples indicating infection by BVDV-1 and not BVDV-2, BVDV-3, or Border disease virus. The molecular characteristics of the 5′-untranslated region (5′-UTR) of BVDV-1 were recognized as belonging predominantly to the BVDV-1a, 1b, 1c, 1m, and 1p subtypes. BVDV-1b and 1m were the most abundant subtypes identified in this region, similar to the BVDV epidemics in cattle in other regions of China. This is the first study that describes the genetic characterization of BVDV in sick goats from southwestern China and is important for future studies and control programs.